Basic self-disorders may play a role in the development of depression in schizophrenia: a seven-year follow-up study - Haug, Elisabeth; Øie, Merete Glenne; Svendsen, Ingrid Hartveit; Møller, Paul; Nelson, Barnaby; Melle, Ingrid (Frontiers in Psychiatry, 2025)
IntroductionDepression is the most common co-morbid psychiatric disorder in patients with schizophrenia and has a negative effect on functional outcomes and quality of life. There are several possible pathways leading to depressive symptoms in schizophrenia. Self-disorders are disturbances in the deepest, pre-reflective level of the self and are suggested to be core features of schizophrenia. The relationship between self-disorders, and depressive symptoms has only been studied to a limited extent, and there are no longitudinal studies. This study aimed to explore the relationship between self-disorders at baseline and the development of depression over the follow-up periodMethodsSelf-disorders were examined with the Examination of Anomalous Self-Experience (EASE) instrument in 31 patients with schizophrenia during their first treatment. Seven years later we measured the total number of depressive episodes since the start of treatment.ResultsWe found a clear association between self-disorders at baseline and the total number of depressive episodes over the follow-up period.DiscussionSelf-disorders may play a role in the development of depression in schizophrenia. This may have implications for therapeutic approaches targeting a condition that is characterized by considerable suffering and an elevated risk of suicide.